Efektivitas Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Kecamatan Kabupaten Gorontalo - Labaso, Dela Puspita; Abdussamad, Juriko; Tui, Fenti Prihatini Dance (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2025)
This study aims to evaluate the effectiveness of the community-based drinking water supply and sanitation program (PAMSIMAS) in Telaga Biru District, Gorontalo Regency, focusing on three villages: Modelidu, Ulapato A, and Ulapato B. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. The results show that the effectiveness of the program varies in each village, namely Modelidu and Ulapato A villages, the program has not been fully effective due to weak institutional management, low community participation, and limited infrastructure maintenance. Meanwhile, Ulapato B village shows successful program implementation with routine maintenance, good water quality, and active community participation. These findings indicate that the sustainability of the program is highly dependent on community participation, strengthening village institutions, and ongoing technical and policy support. This study recommends revitalizing management institutions and increasing community capacity as keys to the effectiveness of the community-based drinking water supply and sanitation program (PAMSIMAS) in rural areas.